2013
DOI: 10.1111/ijau.12010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Audit Fee Discounts on Audit Quality: Evidence from Germany

Abstract: We examine the presence and magnitude of initial audit engagement fee cutting and its potential effect on audit quality in Germany using a sample of 992 firm‐year observations from 2005 through 2011. Our results show systematic fee cutting for initial audit engagement years in Germany. Despite significant audit fee differences between initial and subsequent audit engagement years, we do not find differences in audit quality. Overall, our findings support prior empirical studies, suggesting that low‐balling is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…In line with Dobler (), SWITCH is insignificant throughout all estimations, which may indicate that neither audit fee premiums nor audit fee discounts are prevalent in cases of a (rather unusual) switch in the sample. Overall, the R 2 of 58.53% indicates a lower fit than most international and German audit fee models for listed audit clients (e.g., Antle et al, ; Köhler et al, ; Krauss et al, ); however, it is slightly higher than Chaney et al’s () R 2 of 57%, but clearly below Clatworthy et al’s () R 2 of 78% for private firms. The variance inflation factors are clearly below 10, with a mean of 1.2, indicating no multicollinearity concerns in the multivariate setting.…”
Section: Regression Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…In line with Dobler (), SWITCH is insignificant throughout all estimations, which may indicate that neither audit fee premiums nor audit fee discounts are prevalent in cases of a (rather unusual) switch in the sample. Overall, the R 2 of 58.53% indicates a lower fit than most international and German audit fee models for listed audit clients (e.g., Antle et al, ; Köhler et al, ; Krauss et al, ); however, it is slightly higher than Chaney et al’s () R 2 of 57%, but clearly below Clatworthy et al’s () R 2 of 78% for private firms. The variance inflation factors are clearly below 10, with a mean of 1.2, indicating no multicollinearity concerns in the multivariate setting.…”
Section: Regression Resultsmentioning
confidence: 63%
“…A meta‐regression approach used by Hay and Knechel () showed that despite a publication bias that tends to overstate the Big 4 audit fee premium, such a premium is still regularly found, most likely in the nongovernmental sector and in US settings but not for private audit clients (“nonstandard entities”). Bigus and Zimmermann (), Köhler, Marten, Ratzinger‐Sakel, and Wagner (), and Fleischer and Goettsche () provided German evidence on a Big 4 audit fee premium, whereas Krauss, Quosigk, and Zülch () did not report a Big 4 audit fee premium in the market for listed audit clients in Germany. Joha and Günther () found significant Big 4 audit fee premiums for private and public audit clients.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As the first assumption, Dye (1991) indicates that the client is able to exploit this bargaining power in order to capture the entire cost savings. Accordingly, the author assumes that low-balling practices disappear as a result of getting the auditor to lower the audit fees and accept zero quasi-rent (Ghosh and Lustgarten, 2006;Krauß et al, 2014). Ghosh and Lustgarten (2006) regard cost savings as a 'pie' that could be shared equally or non-equally between the auditor and client, depending on the level of bargaining power between the auditor (monopoly power) and client firm (monopsony power).…”
Section: Future Restatements and Abafeementioning
confidence: 99%
“…Ghosh and Lustgarten (2006) regard cost savings as a 'pie' that could be shared equally or non-equally between the auditor and client, depending on the level of bargaining power between the auditor (monopoly power) and client firm (monopsony power). Dye (1991) also assumes that mandatory disclosure regime of audit fees is likely to stimulate the quasi-rents because the clients have an incentive to pay quasi-rents to influence auditor decision making when they are not publicly disclosed for third parties (Krauß et al, 2014). Therefore, it is concluded that low-balling practices are not likely to happen under a mandatory disclosure regime of audit fees (Dye, 1991;Krauß et al, 2014).…”
Section: Future Restatements and Abafeementioning
confidence: 99%